الدلالة التكرارية في خمريات أبي نواس - احمد خلف, سلام (Al-Adab Journal, 2018)
Repetition is a graphic machine with functions no less important than brevity; yet, it is an artistic refuge that the creator focuses on when he is informed of the message for the report and the effective rhythm of the report.This is why I wanted to study the graphic, aesthetic, and rhythmic act of stylistic repetition; I chose a set of poetic models by focusing on the geometry of repetition and its location in the text and the crisis and its numerous formations accompanied by a flood of poetic and image literatures and imagination; the repetition of poetry strengthens unity and concentration It appears in the rotation of motion and sleep or repetition of the thing on equal dimensions. And in the repetition of one word or one meaning of the rewind, rewind the beginning in the end, rewind the decision to sing, the return of the deficit on the chest in the hair, rewind the note in music, and the frequent return to a certain thing. And repetition is very common in art and less, we find a technical effect is not repeated parts of the close or divergent. And from the consistent rewind or rhythm.This is why we find a repetition that affects the title and its significance and gives the text and the speech harmony and cohesion in building it thanks to repetition because it is the fine thread and the dramatic spirit that preserves all these models, but there is a very strong relationship between That graphic act and the recipient interacted with the message